Potential biomarkers for predicting the risk of thyroid cancer in immunosenescence: a population-based and externally validated multi omics study - Li, Qian; Zhao, Yuanyuan; Yan, Jiawei; He, Chao (Frontiers in Oncology, 2025)
ObjectivesGenome-wide association studies (GWAS) have pinpointed several risk loci linked to thyroid cancer; however, the discovery of new plasma proteins implicated in immunosenescence continues to pose significant challenges. This study aims to uncover novel plasma proteins tied to aging, potentially contributing to thyroid cancer, utilizing diverse investigative methodologies.MethodsIn this research, we utilized an integrative omics approach to identify novel plasma proteins associated with immunosenescence in relation to the risk of thyroid cancer. Additionally, we performed meta-analyses to pinpoint loci and genes affected by pleiotropic effects. Finally, complementary results were obtained from an independent cohort analyzed at Chongqing Medical University Yongchuan Hospital and Bulk-RNA seq from GEO database.ResultsCausal analysis suggests that DNA methylation age acceleration as measured by the Hannum method increases the risk of thyroid cancer (OR: 1.126, 95% CI: 1.002-1.265, P=0.046). Subsequently, we conducted a meta-analysis on the relationship between Hannum DNA methylation age and thyroid cancer risk, which identified 138 potential risk loci through FUMA. Additionally, proteomics and transcriptomics collectively identified 6 potential targets related to immunosenescence and thyroid cancer. Subsequently, Bulk-seq results indicated differential expression of GFRA2 and LILRA2 genes in thyroid cancer. Finally, analyses from an independent cohort at the Second Affiliated Hospital of Chongqing Medical University also demonstrated high expression of LILRA2 in thyroid cancer patients.ConclusionsThis study identified novel plasma proteins associated with immunosenescence that may be linked to thyroid cancer development. These findings enhance our understanding of the immunosenescence-thyroid cancer link and support future diagnostic and therapeutic developments.